2021
DOI: 10.21608/amj.2021.178262
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Outcome and Vaginal Delivery Rates Among Primigravidae With Unengaged Head at Onset of Labor

Abstract: Background:The criteria for diagnosing delivery disorders in the first and second stages of labor remain controversial. It is generally accepted that an elevated position of the fetus in primigravidas during short-term labor may indicate a threat to normal progression of labor due to fetal-pelvic disproportion or obstruction of the fetal passage by tumor or placenta.Objective: To determine fetal outcome and vaginal delivery rates among primigravida with unengaged head at onset of labor.Patients and Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…10 The results of our study showed mean birth weight of 3.01kg. El-Desouky ESAS et al 11 in their study of engaged versus unengaged fetal heads in primigravida women reported a mean birth weight of 3kg which is consistent with the findings of our study. Ashwal E et al in their study described a birth weight of 3.2 kg.…”
Section: Discussionsupporting
confidence: 92%
“…10 The results of our study showed mean birth weight of 3.01kg. El-Desouky ESAS et al 11 in their study of engaged versus unengaged fetal heads in primigravida women reported a mean birth weight of 3kg which is consistent with the findings of our study. Ashwal E et al in their study described a birth weight of 3.2 kg.…”
Section: Discussionsupporting
confidence: 92%